An Assessment of a Shortened Consent Form for the Storage and Research Use of Residual Newborn Screening Blood Spots. (December 2017) - Rothwell, Erin; Goldenberg, Aaron; Johnson, Erin; Riches, Naomi; Tarini, Beth; Botkin, Jeffrey R.
As state newborn screening programs develop approaches to parental permission for the storage and use of residual dried newborn screening samples, it is important to understand how the public comprehends the consent elements. Focus groups in Utah, California, and Michigan ( n = 7 groups, 69 participants) were conducted to evaluate the language on a shortened consent form. Outcomes from the analysis included barriers to conceptualizing biospecimen research, the overly cautious tone and awkwardness of the consent form, and perceptions of community versus individual benefit. This research offers insight on public response to, and comprehension of, commonly used consent language for the storage and use of dried blood spot research in a shortened consent form.